Pembiayaan Optimal dan Korelasinya Terhadap Alokasi Pembiayaan pada Bank Umum Syariah di Indonesia - Ernawati Ernawati; Mansyur Asri (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
Islamic Commercial Banks in Indonesia behave risk averse, which is indicated by financing based on murabaha. The focus of this research is to examine the composition of optimal financing and its correlation to the allocation of financing at the Islamic Commercial Bank. The research data was obtained through the publication of the Indonesian Financial Services Authority with an analysis period of June 2014 to December 2017. There were 13 types of financing allocated by Sharia commercial banks in Indonesia, but based on the completeness of the data, the types of financing estimated were 9 types. Data analysis is used with the mean variance and correlation. Calculation of data using the Excel Solver program. The results showed: (1) the composition of optimal financing at the Islamic Commercial Bank consisted of seven types of financing, and was based on four main groups, namely: mudharaba rupiah, murabaha forex, murabaha rupiah, and istisna rupiah; and (2) the composition of optimal financing and the composition of financing allocations to Islamic banks showed a low correlation; and (3) qardh financing which is the last ranking in the optimal portfolio composition, is still prioritized by Islamic Commercial Banks; driven by the sharia function on adapts non-commercial purposes.